Efficacy of Combination Therapy of Statin and Vitamin C in Comparison with Statin in the Prevention of Post-CABG Atrial Fibrillation - Jahanbakhsh Samadikhah; Samad EJ Golzari; Babak Sabermarouf; Ida karimzadeh; Parastou Tizro; Hadi Mohammad Khanli; Kamyar Ghabili (Tabriz University of Medical Sciences, 2014)
Purpose: Atrial fibrillation (AF) is the most frequent arrhythmia that follows coronary artery bypass graft (CABG). Patients developing postoperative AF (POAF) have significantly higher mortality rates. The consistent prophylactic effectiveness of statins and vitamin C are well-accepted; however, no evaluation on combined therapy has been performed. We aimed at assessing the efficacy of combination therapy with statin and vitamin C in comparison with statin alone in the prevention of post CABG-AF. Methods: In a randomized double blind clinical trial, 120 candidates of CABG were recruited in Tabriz Madani Educational Center in a 15-month period of time. Patients were randomized into two groups of 60 receiving oral atorvastatin (40mg) plus oral vitamin C (2g/d operation day and 1g/d for five consequent days) for intervention group and oral atorvastatin (40mg) for control group. Occurrence of post CABG AF was compared between the two groups. Results: There were 60 patients, 43 males and 17 females with a mean age of 61.0±11.5 (29-78) years, in the intervention group and sixty patients, 39 males and 21 females with a mean age of 60.5±11.3 (39-81) years, in the control group. The post CABG AF occurred in 6 cases (10%) in the interventional group and 15 patients (25%) in the controls (P=0.03, odds ratio=0.33, 95% confidence interval 0.12-0.93). Conclusion: Based on our findings, combination prophylaxis against post CABG AF with oral atorvastatin plus vitamin C is significantly more effective than single oral atorvastatin.